Artificial Intelligence in the Classroom: Revolutionizing English Language Teaching - Tiwari, Hari Prasad (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
This qualitative study investigates the integration of Artificial Intelligence (AI) in English Language Teaching (ELT) within university settings, with a specific focus on the viewpoints and experiences of university-level English teachers in Nepal. The research was conducted in Lumbini Province, Nepal, where 14 university-level English teachers were purposively selected from seven constituent campuses. Through unstructured smartphone interviews, participants shared insights on AI integration in ELT. The findings reveal a diverse range of expectations and concerns among university-level English teachers regarding AI’s role in language instruction. While participants expressed optimism about AI’s potential to revolutionize language learning through personalized experiences and immediate feedback, they also voiced apprehensions. These concerns encompassed job displacement, potential erosion of human interaction, and ethical implications related to AI usage. To address these challenges, participants employed various strategies. They navigated ethical considerations by raising awareness, engaging in reflection, and advocating for ethical guidelines. The study emphasizes the importance of a balanced approach to AI integration-one that harnesses its promises while addressing potential pitfalls. Responsible and inclusive AI usage in language education necessitates thoughtful consideration of both benefits and challenges.